Beyond Borders, Beyond Barriers: Globalization’s Contradictory Role in Women’s Economic Empowerment (Journal of Asian Development Studies, 2025)
In the era of deepening global integration, this study examines how economic globalization, measured by trade openness and foreign direct investment (FDI), shapes women’s economic rights across 160 countries (1996-2023). The study constructs a composite women’s economic rights index using the Cingranelli-Richards (CIRI) framework (an ordinal 0–3 scale capturing legal guarantees of equal pay, nondiscrimination, workplace protections, and occupational choice) and employs ordered logistic regression to respect the index’s discrete nature. Key independent variables are trade openness and FDI, while control variables include GDP per capita, democracy level, fertility rate, female labor force participation, and female population share. The study results indicate that greater trade openness significantly increases the likelihood that women enjoy stronger economic rights, whereas higher foreign direct investment (FDI) inflows are associated with weaker rights. Among domestic factors, higher per capita GDP and a larger female labor force are associated with enhanced economic rights, whereas higher fertility rates tend to diminish them. These findings suggest that trade liberalization can catalyze women’s empowerment; however, the positive effects of FDI depend on the presence of robust, gender-sensitive policies and institutions. To translate globalization into gender-equal outcomes, policymakers should strengthen democratic institutions and media freedom to amplify women’s voices, regulate FDI under clear gender-equality standards, and invest in supportive programs, including childcare, education, and workplace safety, to boost female labor participation. By revealing the nuanced interplay of global and domestic forces shaping women’s rights, this study provides a critical evidence base for achieving inclusive development in the global economy.